KOMUNIKASI PEMASARAN SENTANA ART DALAM MEMPROMOSIKAN DAN MENJUAL PRODUK ALAT MUSIK KE MANCANEGARA - Hendrawan, Titan Venus; Riyanto, Buddy; Muadz, Muadz (Solidaritas, 2024)
Sentana Art is a musical instrument craftsman company that is less appreciated and does not get the right market in Indonesia, due to limited human resources and lack of availability of raw materials so that it cannot meet the demand of the Indonesian market. Therefore, Sentana Art carries out marketing activities abroad because it has a vision and mission in preserving Indonesian culture. Sentana Art carries out marketing activities with a series of musical performances in various parts of the world. The purpose of this study is to describe Sentana Art's marketing communication activities in promoting and selling its products abroad. This study is descriptive qualitative with the determination of informants through purposive sampling. This study uses the theory of integrated marketing communication elements from Kotler & Keller. Data collection methods through interviews, observations and documentation. Data analysis techniques using the Miles & Hubberman method. The results of this study are Sentana Art's marketing communications with a series of events from musical performances, exhibitions, workshops, press conferences, and digital works, through Events & Sponsorships. Public Relations and Publicity. Interactive Marketing. Personal Selling. Word of Mouth Marketing with feedback and recommendations from visitors on the series of music performances held. The results of marketing communications carried out with the sale of all products abroad, as well as getting many offers of work relationships and collaborations for music performances to follow. Keywords: Marketing communications, Integrated Marketing Communication Elements, Music performances, Product Sales, Work Relationships